Two new sympatric troglobitic freshwater flatworms (Platyhelminthes: Dugesiidae) from a hotspot of subterranean biodiversity in the Neotropics - Hellmann, Lindsey; Leal-Zanchet, Ana Maria; Ferreira, Rodrigo Lopes (Zootaxa, 2018)
The Areias System, situated in the Atlantic Forest, is considered a hotspot of troglobitic diversity in Brazil. Herein we describe two new sympatric, troglobitic species of Girardia occurring in this system. Both species show minute eyes; one of them has a whitish body, and the other scattered, fine pigmentation over the dorsal surface. Regarding the copulatory apparatus, one of the species shows a bulbar cavity with multiple diverticula and a bursal canal of the angled type, whereas the other has a single, ovoid bulbar cavity and a smoothly curved bursal canal, among other distinguishing features. Thus, each species can be differentiated by a unique combination of features in its external morphology and copulatory apparatus. Both present a restricted distribution, occurring in a group of pools in travertine rock formed by water from the epikarst. The morphological features of both species and this sampling location indicate that both species are stygobionts